Micronutrient Deficiencies and Anemia in Children with Inflammatory Bowel Disease - Julie Rempel (Nutrients, 2021)
Children with inflammatory bowel disease (IBD) are at risk of developing nutrition deficiencies, particularly because of reduced intake, restrictive diets, malabsorption, and excessive nutrient loss. The aim of this study was to determine the prevalence and predictors of anemia and micronutrient deficiencies at diagnosis and one year follow up in children and adolescents with inflammatory bowel disease (IBD). Children and young adults diagnosed with IBD before the age of 17 years between 2012 and 2018 were included. Laboratory measurements including serum levels of iron, ferritin, zinc, vitamin D, vitamin A, vitamin E, selenium, copper, vitamin B12, and red blood cell (RBC) folate at diagnosis and one-year follow-up were documented as part of the Manitoba Longitudinal Pediatric Inflammatory Bowel Disease (MALPID) Cohort. A total of 165 patients with IBD were included, 87 (53%) with Crohn’s disease (CD) and 78 (47%) with ulcerative colitis (UC). The prevalence of deficiencies in our cohort at diagnosis and one year follow-up, respectively, were iron (56% and 27%), ferritin (39% and 27%), zinc (10% and 6%), vitamin D (22% and 13%), vitamin A (25% and 25%), vitamin E (5% and 4%), selenium (10 and 7%), copper (17% and 27%), vitamin B12 (2% and 5%), and Red blood cell (RBC) folate (1% and 17%). Anemia was present in 57% and 25% at diagnosis and follow up respectively. In CD patients, age of diagnosis (15y–younger than 18y) was a predictor of moderate to severe anemia and albumin levels (<33 g/L) were protective against anemia. Many children with IBD suffer from anemia and micronutrient deficiencies at diagnosis and some fail to recover after one year despite being in clinical remission.